The Effects of Computer-assisted L1 and L2 Textual and Audio Glosses on Vocabulary Learning and Reading Comprehension across Different Learning Styles - Mojtaba Tadayonifar (National Research University Higher School of Economics, 2021)
The current study investigated the effects of computer-assisted L1 and L2 textual and audio glosses on vocabulary learning and reading comprehension across various learning styles. Based on the PET test, 30 homogeneous Iranian EFL learners took the VARK questionnaire and were divided into five learning style groups. Twenty-eight words were selected to be glossed in four reading passages. The selected passages, which were glossed in the four different forms of L1 and L2 audio and L1 and L2 textual by creating hyperlinks on the target words, were presented to the participants through a computer screen. All groups underwent all the treatment conditions and then took posttests. Three-way ANOVAs were run to investigate the effects of learning styles, modes, and language, and their two-way and three-way interactions on the performance of EFL learners on the vocabulary and reading comprehension posttests. While no significant differences between language and mode of glosses on the reading comprehension posttest scores were observed, it was revealed that L1 glosses were more beneficial than L2 glosses for vocabulary learning. The study also showed that the textual glosses were more effective than audio glosses for vocabulary learning. The results further displayed significant differences between learning styles on the vocabulary learning and reading comprehension posttest scores.